Work and injuries in dancers: Survey of a professional dance company in Brazil - Scialom, M.; Goncalves, A.; Padovani, C. R. (Science & Medicine Inc, 2006)
This study examined the daily life and most important physical injuries suffered and reported by the dancers of a professional (contemporary) dance company in S (a) over tilde $o Paulo, Brazil. Through an observational, cross,sectional, retrospective procedure using a questionnaire that collected qualitative and quantitative data, we were able to gather information on 30 dancers who collaborated with the survey. We determined that the injuries considered as most important by dancers were those that prevented dance activity during some months. These injuries occurred mainly during rehearsals (which is the activity occuppying, the most time on the schedule). Articular injuries were the most frequent and mainly involved the knee and ankle. They were related to classical technique, in which most of the company's artists started their dance careers. Medical care usually was sought within 1 day, and the prescribed treatment resolved the problem, but the injury cause was not identified in all cases.